Dialogue-Thermal Comfort: Investigation Through Body Behavior in Kampung Deret Petogogan - Kevin Tanamas; Samsu Hendra Siwi; Fermanto Lianto; Martinus Bambang S (International Journal of Built Environment and Scientific Research, 2020)
This paper explores the relationship between thermal comfort with body behavior. Thermal comfort which is usually measured using a thermo hygrometer, but in this paper the author will more focus on analyzing the body behavior of the occupants in identifying spaces that are comfortably and thermal discomfort. The classification of spaces, elements, and occupants’ activities that will affects the level of thermal comfort here. This study took three sample houses as a representation in the Kampung Deret Petogogan, using in-depth interviews, observing the body behavior of the occupants and the researches. The purpose of this research is to get an answer from the use of RISHA House in the Kampung Deret Petogogan which is a government program that can provide thermal comfort for the occupants. The results of this research are expected to be a guideline for government to developing RISHA House in the future.